A Systematic Literature Review of Empathy Development: Effective Strategies for Overcoming Bullying in Students - I Komang Mertayasa (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2024)
The number of bullying cases in the school environment, studies related to prevention efforts, and the importance of empathy in preventing bullying behavior emphasize the urgency of conducting literature reviews. This is done to find out how empathy can prevent bullying and how education should be carried out so that students become anti-bullying. A review of the literature provides effective strategies that can be widely implemented to prevent bullying and support positive social development for the entire school community. Research was carried out on the selected articles through the selection stages that had been set, so that eight articles were produced for analysis. Results of the analysis show that empathy plays a crucial role in overcoming bullying behavior in the school environment by improving students' emotional understanding, encouraging pro-social behavior, reducing aggression, and increasing social responsibility. Empathy can help students better understand and feel the emotions of others, which in turn reduces the tendency to act aggressively and increases appreciation for the feelings and perspectives of others. Teachers have an important role in minimizing bullying by integrating empathy into the curriculum and using interactive methods. Structured and continuous empathy training, as well as an increase in students' emotional intelligence, are effective in preventing bullying behavior. A proactive counseling approach, the creation of a supportive school environment, and the involvement of parents and the community in anti-bullying programs strengthen student character building and create a safe and inclusive environment. The collaborative implementation of these programs can have a long-term impact on preventing bullying and building more positive social relationships.